Museum documentation and religiosity: the case of the collection of textile garments of the marian image of dressing of the Convent of Our Lady of Penha Museum - ES (Revista de Ensino em Artes, Moda e Design, 2025)
The research theme in the cultural panorama is dedicated to the collection of textile garments of the dress image of Our Lady of Penha, belonging to the Museum of the Convent of Our Lady of Penha, in its symbolic representations. The investigation focuses on the study and application of musealization, specifically museological documentation, a specialized conceptual and practical process in the field of Museology. The problem involves the informational and symbolic gap at the textile garments and the institutional preservation processes undertaken in the pieces, highlighting the museological documentation of the project entitled Inventory and preventive conservation of textile garments from the sculptural collection of the Convent of Penha, in Vila Velha - ES, year of 2023. In the study of the morphological characteristics and meanings, resources from Iconography and Iconology were used together with religious orientations and Museology, Information Science (Documentation), Arts and Social Memory. The research, in its finals considerations, concludes that the application of the musealization process in the collection of textile garments, which has the character of integrating sociocultural aspects of religiosity in the objects, allows the preservation, safeguarding and museological documentation of the capixaba catholic memory of the materials, full of immaterial meanings, in the Convent of Our Lady of Penha Museum.
Keywords: musealization; museological documentation; symbolic value; sacred textile garments; museum of the convent of our Lady of Penha